Factors contributing to the pedal error or pedal misplacement among malaysian car drivers : A survey - Mohamad Zairi, Baharom; Zulkifli, Ahmad@Manap; Nursya Mimie Ayuny, Ismail; Mohd Hasnun Ariff, Hassan; Karjanto, Juffrizal; Khairil Anwar, Abu Kassim (Springer Science and Business Media Deutschland GmbH, 2023)
The driver’s foot movement is unpredictable, which could lead to an error in foot placement. The farther the foot is from the target pedal, the more likely it is to make an error while pressing the pedal. The purpose of this study is to identify the mistakes and factors that contribute to incorrect pedal placement among Malaysian drivers. In addition, to learn more about the elements which cause road accidents in Malaysia. An online survey was carried out to collect the data for the study using the Google Form platform. According to the survey, the study was successful in determining foot placement on the pedal by Malaysian drivers when driving, as well as the factors, which contribute to incorrect foot placement on the pedal and road accidents in Malaysia. A total of 321 responses with age range between 20 and 60 years old participated in the survey. Based on the survey, 10% of the respondents are using both legs while driving and use their left foot to press the brake pedal in an automatic transmission car. The study also discovered various sources and causes that contribute to Malaysian drivers’ wrong pedal placement, including being surprised, interrupted, and confused.